2021
DOI: 10.1002/ece3.7505
|View full text |Cite
|
Sign up to set email alerts
|

Valley‐scale hydrogeomorphology drives river fish assemblage variation in Mongolia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Our results showed that geomorphology has a strong influence on fish assemblages in US forested and endorheic rivers and in Mongolia endorheic rivers, confirming recent results showing how changes in valley‐scale geomorphology drives changes in fish assemblages in river macrosystems (Maasri et al, 2021). Geomorphic variables that were important in predicting fish occurrences tended to distinguish reaches based on valley width and gradient.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results showed that geomorphology has a strong influence on fish assemblages in US forested and endorheic rivers and in Mongolia endorheic rivers, confirming recent results showing how changes in valley‐scale geomorphology drives changes in fish assemblages in river macrosystems (Maasri et al, 2021). Geomorphic variables that were important in predicting fish occurrences tended to distinguish reaches based on valley width and gradient.…”
Section: Discussionsupporting
confidence: 91%
“…We used the ArcGIS‐based geomorphic model RESonate to identify distinctive reaches or FPZs separately in Mongolia and western North America mountain and endorheic ecosystems, following Williams et al (2013) and Maasri et al (2021). This is a GIS approach to identify unique river reaches using variables that are available in online GIS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations